Jalur Pembangunan Sosial: Misi Gereja di Poso Kota Bersaudara Dalam Pemulihan Poso Setelah Seperempat Abad Pascakonflik: The Path of Social Development: The Church's Mission in Poso City for the Restoration of Poso After a Quarter-Century Post-Conflict - Pieter G.O. Sunkudon (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
This research aims to provide an in-depth and holistic understanding of the role of the Christian Church in post-conflict social development in Poso, as well as detailing an evaluation of the successes or challenges faced by the Christian church in achieving its social development mission after 25 years after conflict. The results of this research have significant implications for the role and responsibilities of the Church in the context of social development missions in the Poso and perhaps also in other conflict contexts. The information and findings obtained from this research can be the basis for formulating more effective and sustainable strategies in supporting social development purposes in the region. It is hoped that the implications of the research results can provide input for churches and governments in designing more effective, sustainable social development programs in the future. This article contributes by providing a comprehensive understanding of the role, successes, and challenges of the Christian Church in post-conflict social development in Poso, while offering practical implications for churches and governments in designing more effective and sustainable recovery strategies. Penelitian ini bertujuan untuk memberikan pemahaman yang mendalam dan menyeluruh tentang peran Gereja Kristen dalam pembangunan sosial pasca konflik di Poso, serta merinci evaluasi terhadap keberhasilan atau tantangan yang dihadapi oleh gereja Kristen dalam mencapai misi pembangunan sosial setelah 25 tahun pasca konflik. Hasil penelitian ini memiliki implikasi yang signifikan terhadap peran dan tanggung jawab Gereja dalam konteks misi pembangunan sosial di Poso dan mungkin juga di daerah-daerah konflik lainnya. Informasi dan temuan yang diperoleh dari penelitian ini dapat menjadi dasar untuk merumuskan strategi yang lebih efektif dan berkelanjutan dalam mendukung tujuan pembangunan sosial di wilayah tersebut. Diharapkan implikasi dari hasil penelitian ini dapat menjadi masukan bagi gereja dan pemerintah dalam merancang program-program pembangunan sosial yang lebih efektif dan berkelanjutan di masa depan. Artikel ini berkontribusi dengan memberikan pemahaman komprehensif mengenai peran, keberhasilan, dan tantangan Gereja Kristen dalam pembangunan sosial pascakonflik di Poso, serta menawarkan implikasi praktis bagi gereja dan pemerintah dalam merancang strategi pemulihan yang lebih efektif dan berkelanjutan.